2011
DOI: 10.1293/tox.24.63
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Carcinosarcoma in a 2-year-old Female Wistar Hannover GALAS Rat

Abstract: Carcinosarcomas are rare tumors in humans as well as rats and most commonly occur in the uterus. Recently, we observed a case of incidental carcinosarcoma of the uterus in a female Wistar Hannover GALAS [BrlHan:WIST@ Jcl (GALAS)] rat at 2 years of age. Histopathologically, the tumor was characterized by an admixture of malignant epithelial and nonepithelial elements. The carcinomatous components represented a type of endometrial carcinoma, consisting of glandul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Heterologous types contain mesenchymal tissues not normally present in the uterus, such as skeletal muscle, cartilage, or bone (Figure 11D). MMMT is a very rare, spontaneous neoplasm in animals and has been previously diagnosed in one cat (Nicotina, Zanghi, and Catone 2002), one rabbit (Goto et al 2006), five Lewis rats (Kaspareit-Rittinghausen and Deerberg 1990), and three Wistar rats (Takami et al 2011; Van den Brink-Knol and van Esch 2010), though it has never been reported as a treatment-related finding in animals.…”
Section: Challenging Rat Uterine Neoplasmsmentioning
confidence: 99%
“…Heterologous types contain mesenchymal tissues not normally present in the uterus, such as skeletal muscle, cartilage, or bone (Figure 11D). MMMT is a very rare, spontaneous neoplasm in animals and has been previously diagnosed in one cat (Nicotina, Zanghi, and Catone 2002), one rabbit (Goto et al 2006), five Lewis rats (Kaspareit-Rittinghausen and Deerberg 1990), and three Wistar rats (Takami et al 2011; Van den Brink-Knol and van Esch 2010), though it has never been reported as a treatment-related finding in animals.…”
Section: Challenging Rat Uterine Neoplasmsmentioning
confidence: 99%